Hubungan Kehilangan Gigi dengan Status Gizi dan Kualitas Hidup pada Lansia di Kecamatan Balikpapan Timur - Ramadhana, Gusti N.; Irsal, Imran; Fitriany, Evi (e-GiGi, 2025)
Abstract: Long life without being balanced with health is not meaningful enough. One of the oral health problems in the elderly is tooth loss. Reduced number of teeth can have an impact on reducing nutritional status and quality of life in the elderly. This study aimed to determine the relationship between tooth loss with nutritional status and quality of life in the elderly in East Balikpapan Sub-District. This was an analytical observational study with a cross-sectional design. Samples of 100 elderly people in East Balikpapan Sub-District were obtained using a proportionate stratified random sampling technique. Data were collected through oral cavity examination, height and weight measurements, and interviews using the Geriatric Oral Assessment Index (GOHAI) questionnaire. Data were analyzed using the chi-square test. The results showed that there were significant relationships between tooth loss and nutritional status (p=0.005) and between tooth loss and quality of life (p=0.000). In conclusion, there is a significant relationship between tooth loss with nutritional status and quality of life among the elderly people in East Balikpapan Sub-District. Keywords: tooth loss; nutritional status; quality of life; elderly    Abstrak: Usia panjang tanpa diimbangi dengan kesehatan kurang berarti. Masalah kesehatan rongga mulut pada lansia di antaranya ialah kehilangan gigi. Berkurangnya jumlah gigi dalam rongga mulut dapat berdampak pada penurunan status gizi dan kualitas hidup pada lansia. Penelitian ini bertujuan untuk mengetahui hubungan antara kehilangan gigi dengan status gizi dan kualitas hidup pada lansia di Kecamatan Balikpapan Timur. Jenis penelitian ialah observasional analitik dengan desain potong lintang. Sampel berjumlah 100 lanjut usia (lansia) di Kecamatan Balikpapan Timur diperoleh dari teknik pengambilan sampel proportionate stratified random sampling. Data dikumpulkan melalui pemeriksaan rongga mulut, pengukuran tinggi badan dan berat badan, dan wawancara dengan kuesioner Geriatric Oral Assessment Index (GOHAI). Data dianalisis menggunakan uji chi-square. Hasil penelitian menunjukkan terdapat hubungan bermakna antara kehilangan gigi dan status gizi (p=0,005) serta antara kehilangan gigi dan kualitas hidup (p=0,000). Simpulan penelitian ini ialah terdapat hubungan antara kehilangan gigi dengan status gizi dan kualitas hidup pada lansia di Kecamatan Balikpapan Timur. Kata kunci: kehilangan gigi; status gizi; kualitas hidup; lanjut usia